-4x*1x=

Simple and best practice solution for -4x*1x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x*1x= equation:


Simplifying
-4x * 1x = 0

Reorder the terms for easier multiplication:
-4 * 1x * x = 0

Multiply -4 * 1
-4x * x = 0

Multiply x * x
-4x2 = 0

Solving
-4x2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-4'.
x2 = 0

Simplifying
x2 = 0

Take the square root of each side:
x = {0}

See similar equations:

| -4x(x-5)= | | 20x+1=5x-6x | | 12x^2+116x-204=0 | | 8x+6x^2=15x+3x^2 | | 26-3g=8 | | (3i+2j)(7i+9j)= | | 56=-28n | | x+2=3(82-x) | | 3(x+1)(x+1)-(x+3)(2x+2)=0 | | 7x-2=7x+28 | | 8-6x=14-7 | | -8y+32=5-7y | | (x+4)(x+4)-(3x-7)(3x-7)=0 | | 6x+27=-38+47 | | 1.5x-0.33x+0.33+4x+8=180 | | Pi*49= | | ln(x+2)+ln(2x+2)=ln(40) | | ln(x+2)+ln(2x+2)= | | 3(v+8)-5v=14 | | 7(-3y+2)=3(8+7y) | | 6a+b=-3 | | 24-3x=9 | | (9x+7)-(3x-2)= | | 9a+3b+c=4 | | 12-10x=122-45x | | 8y+7=-6y+2 | | 10+4x=3(7x-4)+5x | | -21p^2-24p=12 | | (-x^5)(-x)= | | 10x+2=-2+4 | | 2kx*2kx=0 | | (3x+9)+(6x+7)= |

Equations solver categories